Analysis of The Efficiency of Double E-Barcode Stickers on the Cost and Time of Sterilization at Soedono Hospital - Sarbani Sarbani; Ratna Wardhani; Agusta Dian Ellina; Karina Nur Ramadhaningtyas (Universitas Malahayati, 2026)
ABSTRACT Surgical procedures and invasive procedures in hospitals require the availability of sterile medical instruments and materials in varying quantities and types. However, the trend of increasing healthcare-associated infections (HAIs) remains a major challenge in healthcare facilities. In order to improve the efficiency and quality of service, dr. Soedono Hospital, East Java Province developed the use of a double e-barcode sticker outer indicator as a new labeling system in the sterilization process of medical devices. This study aims to evaluate the influence of the labeling system on the cost and time aspects of sterilization. The research was carried out quantitatively with a comparative design, utilizing secondary data of 200 samples obtained from the sterilization process from 2023 to 2024. The sample consisted of surgical instruments and consumable medical materials sterilized using steam and plasma methods. Data analysis was carried out using Mann-Whitney non-parametric statistical tests to test the difference between the old method and the e-barcode method. The results showed that the application of the double outer indicator of e-barcode stickers did not have a significant impact on sterilization costs (p=0.138), but it was proven to significantly accelerate the sterilization process time (p=0.000). These findings conclude that although costs have not changed much, the time efficiency gained supports improved operational performance, reduced staff workload, and improved patient safety through better tracking and documentation.Keywords: E-Barcode, External Indicator, Sterilization, Cost, Time.